Developing countries' health expenditure information : what exists and what is needed. - NEWBRANDER, William (1994)
Examines existing health expenditure information in terms of its lack of availability and the failure to make use of what is available. Considers what would be desirable issues in establishing data sets, how the data can be used, and the challenges for the future in filling this information gap.